Manganese(II) and Zinc(II) metal complexes of novel bidentate formamide-based Schiff base ligand: synthesis, structural characterization, antioxidant, antibacterial, and in-silico molecular docking study - Juyal, Vijay Kumar; Thakuri, Shweta Chand; Panwar, Mohit; Rashmi,; Prakash, Om; Perveen, Kahkashan; Bukhari, Najat A.; Nand, Viveka (Frontiers in Chemistry, 2024)
A new bidentate Schiff base ligand (C16H16Cl2N4), condensation product of ethylene diamine and 4-chloro N-phenyl formamide, and its metal complexes [M(C16H16Cl2N4)2(OAc)2] (where M = Mn(II) and Zn(II)) were synthesized and characterized using various analytical and spectral techniques, including high-resolution mass spectrometry (HRMS), elemental analysis, ultraviolet–visible (UV–vis), Fourier-transform infrared (FTIR) spectroscopy, AAS, molar conductance, 1H NMR, and powder XRD. All the compounds were non-electrolytes and nanocrystalline. The synthesized compounds were assessed for antioxidant potential by DPPH radical scavenging and FRAP assay, with BHT serving as the positive control. Inhibitory concentration at 50% inhibition (IC50) values were calculated and used for comparative analysis. Furthermore, the prepared compounds were screened for antibacterial activity against two Gram-negative bacteria (Staphylococcus aureus and Bacillus subtilis) and two Gram-positive bacteria (Escherichia coli and Salmonella typhi) using disk-diffusion methods, with amikacin employed as the standard reference. The comparison of inhibition zones revealed that the complexes showed better antibacterial activity than the ligand. To gain insights into the molecular interactions underlying the antibacterial activity, the ligand and complexes were analyzed for their binding affinity with S. aureus tyrosyl–tRNA synthetase (PDB ID: 1JIL) and S. typhi cell membrane protein OmpF complex (PDB ID: 4KR4). These analyses revealed robust interactions, validating the observed antibacterial effects against the tested bacterial strains.